Implementation of Cash Waqf as a Solution for financing Almajiri System Education in Nigeria - Yakubu, Aminu; Binti Abdulaziz, Azreen Hamiza (International Journal of Psychosocial Rehabilitation, 2019)
The Almajiri system of education is one of the great topics of discussion between the scholars and authorities, specifically in the northern parts of Nigeria. The system is one of the child neglect challenges facing the northern states of the country. However, the tradition of the Almajiri system of education is preventing children from having formal education and accepted living standards, which directs the children to bagging and hawking on the street. The purpose of this study is to investigate the causes of child neglect and its effects and to introduce cash waqf as a means of sponsoring the Almajiri system of education. The data for this study was collected through interviews and was transcribed and arranged in themes to ensure that superior points of the responses are mentioned. The findings of this study show that the neglected children were in a dreadful condition that has no excellent future. Poverty and ignorance are the major tools that lead the parents to neglect their children at an early age. Therefore, the following are needed to take these children out of their dreadful condition. The first is to create awareness for parents on the duties and responsibilities established by Islam towards their children. To formalize the Almajiri system of education, which will enable the children to benefit from both Islamic and western education. Implementation of Cash Waqf will also serve as the solution for sponsoring Almajiri education.